Numerical Analysis of Crack Progress in Different Areas of a Friction Stir Welded Bead for an 5251 H14 Aluminum Alloy Specimen - Kambouz, Y.; Benguediab, M.; Bouchouicha, B. (Engineering, Technology & Applied Science Research, 2014)
The assemblies welded by Friction Stir Welding have a major advantage which is the absence of a metal filler. This process contributes to the welding of materials that are known to be difficult to weld using the conventional techniques often employed in the field of transport, for example in the automobile body by applying a spot welding. The numerical modeling of this type of process is complex, not only in terms of the variety of physical phenomena which must be considered, but also because of the experimental procedure that must be followed in order to verify and validate numerical predictions. In this work, a finite element model is proposed in order to simulate the crack propagation under monotonic loading in different areas of the weld seam of a strain hardening CT-50 aluminum alloy 5251H14 specimen.